PENGARUH PEMBELAJARAN JIGSAW TERHADAP KEMAMPUAN MEMECAHKAN MASALAH SISWA KELAS X IPA MA NW SURALAGA TAHUN PELAJARAN 2014/2015 - Indra Himayatul Asri (Cocos Bio, 2016)
This research aimed at knowing the effect of jigsaw learning model on the problem solving about environment pollution of the X IPA grade students of MA NW Suralaga in the school year 2014-2015.This research was experiment utilizing true experimental design in form of post-test only control. The population was all of the X grade students of MA NW Suralaga consisted of 41 students spread in two classes. The sample was X B. It was taken using cluster random sampling. The data collection was done using 5 items description test. The data analysis was done through normality test, homogeneity test, and t-test. The result  of  research  showed that  mean  score in the  posttest  of the experiment class was 66.09 and the control class was 62.36. The result of normality test in the experiment and control class was normally distributed. The experiment class resulted t count (8.595) t table (9.488) and the control class resulted tcount (0.734) X2  table (9.488). The homogeneity showed that both groups werehomogeneous. it can be seen from the value Fcoun(t1.15) Ftable(2.07). The t-test resulted !countttable(3.800 1.708). It can be concluded that utilizing jigsaw had effect on the problem solving ability about environment pollution of the grade X IPA students of MA  NW Suralaga in the school year 20I4-20I5.